The Relationship between Motivation and the Performance of Toddler Integrated Service Post Cadres in the Selogiri Community Health Center Work Area - Erika Dwi Ariyani; Noor Alis Setiyadi (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The role of integrated service post cadres for children under five is very important because they contribute greatly in providing basic health services, providing health-related information to mothers and families, and carrying out activities to monitor children's growth and development. This research aims to determine the relationship between motivation and the performance of integrated service post cadres in the operational area of the Selogiri Health Center. This research methodology uses a quantitative approach with a cross-sectional design. This research started from January to October 2023. The research was carried out at the integrated service post for toddlers in the working area of the Selogiri Health Center. The research population was the entire cadre of integrated service posts for children under five in the Selogiri Community Health Center working area, totalling 450 people. The research sample was 207 respondents, who were surveyed using simple random sampling. Data collection uses a questionnaire. The questionnaire went through a validity and reliability testing stage, which has been tested for validity and reliability. Data were analyzed using the chi-square test, which was analyzed using SPSS version 26 software. The research results showed a statistically significant relationship between motivation and cadre performance (p = <0.001). It is recommended that integrated service post cadres increase further motivation related to implementing integrated service posts so that they can provide better services; It is recommended that community health centres provide support and appreciation to integrated service post cadres to improve cadre performance. Keywords : Cadres, integrated service post, motivation, perfomance, toddler